Studies Of Removal And Recovery Of Palladium From Chloride Media Via An Electrogenerative System - Mansor, Nadia (2019)
The use of palladium nowadays is extensive especially as catalytic converter of vehicles which contributed to increasing demand every year. With the limited source and higher cost in mining and purifying process, palladium is recycled by the industries. However, this precious metal is difficult and required high cost to be treated especially in such low concentration (<500 mg L-1). To overcome this problem, an electrogenerative system was introduced to recover palladium in chloride medium. It is alternative method to other electrochemical methods where the chemical reaction takes place spontaneously in this system since it does not require any external supply of energy. A static batch cell was set up to treat low concentration of palladium in dilute solutions. The dilute chloride with the concentration of 0.1-0.2 M NaCl was optimum to treat palladium with concentration 100-500 mg L-1. A three-dimensional cathode material of reticulated vitreous carbon (RVC) treated with sulphuric acid appeared to give the best performance for optimum palladium deposition. The RVC was found to have low resistance and high mass transfer from supporting analysis using electrochemical impedance spectroscopy and cyclic voltammetry. The generated flow current in this system was supported with a zinc as an anode. Overall, this system showed about >90% of palladium being recovered within 6 h of operation. The reduction of palladium ion was proved by controlled potential using cyclic voltammetry. The deposited palladium on the cathode RVC is visible with naked eyes and was further confirmed by the scanning electron microscopy-energy dispersive Xray spectroscopy.